Acupressure intervention for children: A scoping review - Ramdaniati, Sri; Sitaresmi, Mei Neni; Haryanti, Fitri; Iman, Arief Tarmansyah (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Acupressure is a popular form of complementary nursing among adults. It stimulates the body’s self-healing processes by enhancing energy flow, or “chi,” along meridian channels. Acupressure can address many health issues and is also used on children because it is painless and straightforward. Although acupressure has existed for centuries, research on its applications for children remains limited. Objective: This review aimed to categorize and synthesize the research conducted over 30 years on acupressure in children. Design: A scoping review Data Source: The databases searched were PubMed, ProQuest, Scopus, ScienceDirect, Wiley, Medline EBSCO, and Google Scholar. The inclusion criteria were original peer-reviewed articles in English or Indonesian that used acupressure as an intervention for children in any setting from 1991 until March 2022 and were updated until March 2024. Review Methods: This review followed the Joanna Briggs Institute Manual Methodologies. Subsequently, the retrieved articles were imported into the EndNote program version 20. Based on the identification results, 2924 articles were obtained, and 76 articles were retained. The review decision process was depicted in a PRISMA flow diagram. Results: Of the 76 articles, 72% came from the Asian continent, 66% were published within the past ten years, and 59% were randomized controlled trials. Acupressure was most used (48%) by school-age children (7-12 years), with commonly targeted points being Neiguan (P6), Zusanli (ST36), Hegu (LI4), Yintang (Extra1), and auricular acupoints. Acupressure on children can be administered by acupuncturists, nurses, doctors, caregivers, and parents, offering six main benefits: alleviating nausea and vomiting, relieving pain, decreasing anxiety, relieving fatigue, increasing visual function, and increasing weight and height. Conclusion: Acupressure offers numerous advantages for children with various conditions. Healthcare and nursing professionals should consider using it as a complementary intervention to address issues and problems in healthy and sick children. However, further studies are needed to evaluate its effectiveness.